Ability of Children's Gross Motor Skill Levels: Descriptive Analysis Based on Extracurricular Student Sports - Abdur Rofiq Syafiy; Kartika Septianingrum; Andy Widhiya Bayu Utomo (Universitas Negeri Semarang, 2025)
Knowing students’ motor skills is an integral part of an education. This study aims to determine the level of motor ability of students in the Extracurricular of State Junior High School 2 Bringin . This research is a quantitative descriptive research. The method of this research is by test and measurement techniques. The population in this study is all students of State Junior High School 2 Bringin which totals 120 students who were taken based on purposive sampling techniques, with inclusion criteria that have been determined by the researcher. So that the sample in this study amounted to 40 people. The instruments in this study used the Motor Ability Test which included the 4 x 10 meter Shutlle-run test (agility), the 1-meter distance ball throw test with a wall (coordination), the Stork Stand Positional Balance test (balance), the 30-meter sprint test (speed), with a validity value of 0.930 and reliability of 0.870. Data analysis uses descriptive analysis expressed in the form of percentages. The results of this study show that the motor skills of students in the Extracurricular of State Junior High School 2 Bringin are in the good category. This can be seen in the results of the categories “very lacking” by 6.98%, “less” by 30.23%, “sufficient” by 25.58%, “good” by 32.56%, and “very good” by 4.65%. Based on the results of the study, it can be concluded that gross motor skills in extracurricular students have a good level of skills, but there are some students who are still very lacking. So this makes the implication in this study that the role of teachers in providing stimulus in an effort to improve gross motor skills in students is very important, because the provision of motor stimuli to children will make children more active and reduce stunting rates in Indonesia.